Amikacin, in combination with cations, prevents growth of a carbapenem-resistant/multidrug-resistant Klebsiella pneumoniae strain isolated from a patient with COVID-19 - Magaña, Angel J. (2024)
The most common clinical manifestations of Klebsiella pneumoniae infectionare pneumonia, septicemias, meningitis, and urinary tract or soft tissue infections[1]. Besides being a major cause of neonatal and adult sepsis, K. pneumoniae isalso associated with other diseases like ankylosing spondylitis, liver abscess,and Crohn's disease [1]. The emergence of carbapenem-resistant K.pneumoniae (CRKP) strains has substantially increased morbidity and mortalitydue to infections caused by this bacterium, warranting its placement at the top ofthe World Health Organization's priority list [2]. CRKP-associated mortality ratesin nosocomial infections are as high as 50% [3]. Furthermore, CRKP is within thelist of bacterial pathogens that increased antimicrobial-resistant hospital-onsetinfections by 20% during the COVID-19 pandemic [4].